Further Results on the Constant Elasticity of Variance Call Option Pricing Model - Emanuel, David C.; MacBeth, James D. (Journal of Financial and Quantitative Analysis, 1982)
David C. Emanuel, James D. MacBeth, Further Results on the Constant Elasticity of Variance Call Option Pricing Model, The Journal of Financial and Quantitative Analysis, Vol. 17, No. 4, Proceedings of the 17th Annual Conference of the Western Finance Association, June 16-19, 1982, Portland, Oregon (Nov., 1982), pp. 533-554